American Negro Slavery : A Survey of the Supply, Employment and Control of Negro Labor as Determined by the Plantation Regime - Phillips, Ulrich Bonnell, 1877-1934 (Salt Lake City, UT : Project Gutenberg, 2004)
"American Negro Slavery" by Ulrich Bonnell Phillips is a historical account written in the early 20th century. The book provides a detailed examination of the transatlantic slave trade, focusing on the supply, employment, and systemic control of African labor within the plantation system in America. It endeavors to unpack significant themes around the exploitation and management of enslaved people, with particular emphasis on the economic and social implications of slavery on both sides of the Atlantic. The opening of the work lays a foundation for understanding the origins of the slave trade, beginning with the Portuguese exploration of Guinea in the 15th century. Phillips discusses early encounters between Europeans and Africans, highlighting how initial motivations were framed in terms of moral crusading yet were rapidly eclipsed by commercial greed. By detailing the early capture and transport of Africans to European countries, the text mirrors a narrative of burgeoning exploitation that would expand significantly with the establishment of plantations in the New World. Through a blend of historical context and economic analysis, it sets the stage for a comprehensive discussion about the systemic aspects and impact of slavery on both the enslaved and the institutions that depended on their labor. (This is an automatically generated summary.)
Release date is 2004-03-01
Produced by Juliet Sutherland, Leonard D Johnson and PG Distributed Proofreaders
Keywords: Southern States -- Economic conditions; Slavery -- Economic aspects -- United States; Slave labor; Plantation life -- Southern States